Release characteristics of sediment P in all fractions of Donghu Lake, Wuhan, China. Issue 53 (13th November 2016) - Zhang, Yi; He, Feng; Kong, Lingwei; Liu, Biyun; Zhou, Qiaohong; Wu, Zhenbin
Abstract: The aim of the study was to understand the releasing characteristics of sediment phosphorus (P) in all fractions under varying environmental conditions and the relationship between sediment P and eutrophication in shallow city lake, Donghu Lake of Wuhan in China. Effects of P concentration in overlying water, oxygen, light, pH, temperature, and agitation intensity on release processes of sediment P in all fractions in Donghu Lake, China, were investigated. The release quantity and release rate of sediment P in the distilled water were significantly higher than those of lake water, and under anaerobic condition, they were higher than those of aerobic treatment. The concentrations of each P form decreased obviously in both dark and irradiated systems. Both high and low pH promoted the release of Fe/Al-P, IP, and TP, but Ca-P decreased sharply with decreasing pH, while the difference of OP was not obvious. The release rate of each P form accelerated drastically when water temperature rose from 5 to 30°C. The magnitude of the each P form released increased with the increase in the agitation intensity at the first 6 d, while it showed no significant difference after 8 d in different agitation intensities (100–200 rpm). The results showed that the extent of P in all fractions released from Donghu Lake sediment was affected variously by the environmental factors, and the sediment was unstable, at risk of releasing P to Donghu Lake.